Development of Augmented Reality-Based Digital Teaching Materials on Optical Instruments to Enhance Conceptual Understanding and Project Skills - Indah Saputri; Asrizal Asrizal; Fauziah Ulmi; Annisa N; Aprina Maharani ZAN; Hazrati Ashel (STAI Hubbulwathan Duri, 2025)
Students often struggle with conceptual understanding and project-based skills in physics, particularly in abstract topics such as optical instruments. Traditional teaching methods and limited visualization tools contribute to these difficulties. This study addresses the need for innovative instructional resources by developing digital teaching materials integrated with Augmented Reality (AR) to enhance learning outcomes. This research employed a Research and Development (RD) approach following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Instruments included a needs analysis questionnaire, expert validation sheets, and student practicality questionnaires. Descriptive statistics were used to analyze the data, with validation assessed using Aiken’s V and practicality evaluated using a Likert scale. The developed digital teaching materials underwent expert validation across five components: material substance, visual communication, learning design, software utilization, and AR integration. The average Aiken’s V score was 0.94, indicating high validity. Practicality testing with 35 grade XI students yielded an average score of 96, categorized as